ALTERNATIVE WEAREHOUSES IN LOGISTICS: ALTERNATIVE WEAREHOUSES IN LOGISTICS - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper deals with the potential for meeting the requirements for proper storage in different firms and companies. It analyses the advantages of all kinds of storage, depending on the specific conditions. Different ways of compensating the disadvantages of certain storage are given. Different ways of cost reduction are suggested. Some of them include grouping the cargo units.